Revitalisasi Majelis Taklim dalam Penguatan Literasi Keagamaan dan Moderasi Beragama Berbasis Masjid di RT. 07 Kelurahan Sumur Dewa, Kecamatan Selebar, Kota Bengkulu - Isti Khoma; Laura Saputri; Pegi Puspa Tara; Haryono Haryono; Sutrian Efendi (Yayasan Darussalam Bengkulu, 2026)
Majelis taklim is a mosque-based non-formal Islamic educational institution that plays a strategic role in strengthening community religious literacy, social cohesion, and moderate religious attitudes. However, many majelis taklim experience stagnation due to one-way learning methods, unstructured study materials, weak institutional management, and limited youth involvement in religious learning spaces. This community service program aims to revitalize the mosque-based majelis taklim at RT. 07, Sumur Dewa Village, Selebar District, Bengkulu City, through the integration of religious literacy, religious moderation, institutional strengthening, and simple digital da'wah practices. The program used Participatory Action Research (PAR) involving mosque administrators, religious leaders, majelis taklim members, youth, students, and lecturers as co-participants. The activities were carried out through needs assessment, co-design of thematic curriculum, interactive halaqah, religious literacy training, religious moderation discussions, digital da'wah mentoring, and formative-summative evaluation. The results indicate increased attendance from an average of 18 to 35 participants per session, youth participation from none to an average of 12 participants per session, and a 32.5% increase in participants' religious knowledge based on pre-test and post-test results. Qualitatively, participants became more critical in verifying religious information, more open to dialogue, and more aware of wasathiyah values such as national commitment, tolerance, anti-violence, and accommodation of local wisdom. This program contributes a practical model for revitalizing mosque-based community learning that is inclusive, participatory, and adaptive to contemporary socio-digital challenges.